LIN28‐let‐7 axis regulates genes in immortalized human trophoblast cells by targeting the ARID3B‐complex. Issue 11 (15th August 2019) - Ali, Asghar; Anthony, Russell V.; Bouma, Gerrit J.; Winger, Quinton A.
Abstract : Abnormal placental development is one of the main etiological factors for intrauterine growth restriction (IUGR). Here, we show that LIN28A and LIN28B are significantly lower and lethal‐7 (let‐7) microRNAs (miRNAs) significantly higher in term human IUGR vs. normal placentas. We hypothesize that let‐7 miRNAs regulate genes with known importance for human placental development [high‐mobility group AT‐hook 1 (HMGA1), transcriptional regulator Myc‐like (c‐myc), vascular endothelial growth factor A ( VEGF‐A ), and Wnt family member 1 ( WNT1 )] by targeting the AT‐rich interacting domain (ARID)‐3B complex. ACH‐3P cells with LIN28A and LIN28B knockout (DKOs) significantly increased let‐7 miRNAs, leading to significantly decreased ARID3A, ARID3B, and lysine demethylase 4C (KDM4C). Similarly, Sw.71 cells overexpressing LIN28A and LIN28B (DKIs) significantly decreased let‐7 miRNAs, leading to significantly increased ARID3A, ARID3B, and KDM4C. In ACH‐3P cells, ARID3A, ARID3B, and KDM4C make a triprotein complex [triprotein complex comprising ARID3A, ARID3B, and KDM4C (ARID3B‐complex)] that binds the promoter regions of HMGA1, c‐MYC, VEGF‐A, and WNT1 . ARID3B knockout in ACH‐3P cells disrupted the ARID3B‐complex, leading to a significant decrease in HMGA1, c‐MYC, VEGF‐A, and WNT1. DKOs had a significant reduction, whereas DKIs had a significant increase in HMGA1, c‐MYC, VEGF‐A, and WNT1, potentially due to regulation by the ARID3B‐complex. This is the first study showing regulation of let‐7 targets in immortalized human trophoblast cells by the ARID3B‐complex.—Ali, A., Anthony, R. V., Bouma, G. J., Winger, Q. A. LIN28 ‐let‐7 axis regulates genes in immortalized human trophoblast cells by targeting the ARID3B‐complex. FASEB J. 33, 12348–12363 (2019). www.fasebj.org